Improvement the Strength of a Dental Filling Restoration by Adding of NiTi alloy Powder to Galloy (Medico Legal Update, 2020)
Gallium has the second lowest melting point of all metals after mercury (29.8 ºC) and has the ability to reactwith metals and alloys at room temperature to produce a workable plastic mass that hardens with time. As aresult Gallium-based alloys have been introduced to the dental market as mercury-free amalgam substitutes.Filling material produced by mixing amalgam alloy powder with gallium liquid instead of mercury. Thiswork involves addition of NiTi alloy powder to Galloy to improve some mechanical properties. Theseproperties included compression, hardness, tensile strength and creep. The characterization of preparedNiTi/Galloy with five wt% of addition (1, 2, 3, 4, and 5 wt%) was done by XRD and SEM/EDS. The resultsshowed that the hardness, compression and diametral tensile strength were increased with increasing wt%of added NiTi alloy powder and the creep percent was decreased where NiTinano powder alloy disperses inthe matrix of the alloy and prevents the dislocation movement, also the NiTi powder particles have uniqueproperties of super elasticity that work to increase the creep strength.